Pengembangan Media Dokansi untuk Meningkatkan Motivasi Siswa pada Mata Pelajaran Bahasa Indonesia - Sri Wahyuni Gulo; Nita Septiani Waruwu; Merliani Telaumbanua; Aktif Foera-Era Lase; Arozatulo Bawamenewi (Journal on Education, 2023)
This research was conducted to describe students’ responses in using Dokansi media on fable text material, and the Dokansi’s eligibility as a media on learning fable text material. Using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) methodology, this type of research is known as Development (Research and Development) research. However, the application and evaluation of this research are limited by the information gathered from experts in the media, literature, and academia. This research project was carried out at SMPN. 2 Gunungsitoli. A questionnaire is used to collect data. The subjects in this study were class VII-A. This method is carried out to collect the results of the study and assessment of students’ responses to the media used.